Not all claps and cheers : humor in business and society relationships - Maon, François; Lindgreen, Adam; Vanhamme, Joëlle (Routledge, 2018)
"Scholars from various disciplines have studied humor since antiquity. Yet, over the centuries, these researchers have also struggled to conceptualize a viable, well-accepted notion of humor. Beyond pleasure and amusement, people use humor for a variety of social functions. On the one hand, humor can cause others to like the humorous source more, attract regard, ease conversations, promote expression and the exchange of ideas, introduce new topics of discussion, or smooth interactions. On the other hand, in aggressive forms, humor can halt verbal interactions, modify the usual rules of conversation, communicate critiques, or contribute to the creation of subversive environments. Not All Claps and Cheers: Humor in Business and Society Relationships is an original research anthology that considers different angles from which to address the use of humor by individuals, groups and business actors in their interactions within, around, and across organizationsthat is, at the interfaces of business and society. Accordingly, the research anthology is organized in four sections"Humor, Business and Society," "From Society to Business: Humors Use and Roles in Activist Movements," "From Business to Society: Humors Use and Roles in Marketing, Corporate Communications, and Public Relations," and "Society within Business: Humors Use and Roles in the Workplace and in Organizations." This ground-breaking research anthology draws on material from marketing, communications, human resources and stakeholder theory to throw light on this poorly understood facet of human business behavior."--Provided by publisher.